Development of Digital Literacy-Based Project Based Learning Assessment Models to Improve High School Students' Creative Thinking Abilities - Eliaumra Eliaumra; Dewi Purwasih Samaela; Indri Novayanti Gala; Shelvy Ferawati Rurua (Jurnal Penelitian Pendidikan IPA, 2024)
The use of technology and interactive media in learning is crucial for developing essential information technology and media skills in today's digital era, fostering digital literacy â€“ the ability to understand, use, analyze, evaluate, and participate in the digital world effectively and responsibly.Â  The purposes of this research are to validating a digital literacy-based project-based learning model assessment and enhancing students' digital literacy and creative thinking in high school biology. Using a development research approach and the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), 137 high school students in Poso Regency were sampled. The assessment tools, including observation sheets and rubrics, along with creative thinking tests, demonstrated validity (sig value < 0.05) and reliability (R > 0.60). Implementation revealed excellent digital literacy (86%), good creative thinking (75%), and a moderate improvement (N-gain = 0.68). The assessment's validity and reliability, confirmed through expert and field trials, support its applicability in high school biology learning.